Method for determining in vivo antielastasy activity and effectiveness of treatmental and prophylaxis drugs - Levitsky, A.; Malinovskii, V.; Pavlenko, K.; Yuzkiv, Ya.; Selivanska, I.; Lapinska, A. (Journal of Education, Health and Sport, 2026)
Aim. A method for determining in vivo antielastase activity in rat bone tissue after stress has been proposed. Methods. Stress was reproduced in rats by exposing the animals to −20 °C for 30 minutes. The dietary supplement “EkSoVit” (containing soy extract with proteolysis inhibitors), quercetin and ascorbic acid were used as anti-stressors. Anti-stressors were administered orally 3 days before stress and 3 days after stress. Animals were euthanized on day 4. Results. An increase in elastase activity in the femur of rats after stress was established. All 3 anti-stressors reduce elastase activity: "EkSoVit" by 49 %, quercetin by 136 % and ascorbic acid by 91 %. In terms of anti-elastase efficacy, Quercetin exceeded "EkSoVit" by almost 5 times, and ascorbic acid by three times. Conclusion. Stress causes activation of elastase activity in bone tissue. The main reason for the increase in elastase activity may be the translocation of the enzyme from leukocytes and the intestine. The most active anti-elastase agent was the flavonoid quercetin, which does not have a direct inhibitory effect on the elastase enzyme.